Angle‐Insensitive and CMOS‐Compatible Subwavelength Color Printing. Issue 11 (11th August 2016) - Lee, Kyu‐Tae; Jang, Ji‐Yun; Park, Sang Jin; Ji, Chengang; Yang, Sung‐Mo; Guo, L. Jay; Park, Hui Joon
Abstract : Photonic nanostructures for a wide‐angle and complementary metal‐oxide semiconductor‐compatible structural color printing scheme exploiting strong resonance effects in ultrathin subwavelength semiconductor gratings are demonstrated. The proposed structures create distinctive colors with great homogeneity and high color saturation, easily tuned by varying a width of the subwavelength gratings, thereby enabling individual color pixels to be patterned via one‐step process.